Cryopreservation of transgenic mouse embryos - an eight years’ experience - Wayß, Klaus; Klefenz, Michaela; Schenkel, Johannes (Journal of experimental animal science, 2005)
A total of 70,629 predominantly transgenic mouse embryos prepared from 9,727 pregnant female donors were cryopreserved using a method leading to a high revitalisation rate. Against loss, 125 mutant mouse lines were protected. An average of 7.26 embryos (eight-cell embryos) per pregnant donor was received. To reduce the number of animals required as embryo donors, a special breeding exclusively for cryopreservation was omitted if possible and subsequently the number of animals used for freezing was reduced remarkably. The advantage of this strategy is that (mutant) mouse lines out of current use do not have to be kept in a breeding nucleus. In parallel, this procedure leads to rederivation and improves the export of mice to other facilities. The cryopreservation of these 125 mutant lines keeps the potential to save approximately 20,000 laboratory mice per year to be bred if they were kept in a breeding stock. This is a major contribution to the “3R” requirements developed by Russel and Burch to reduce the number of laboratory animals.
Gesehen am 21.02.2019